Development of an Innovative Online Leave Management System for Human Resource Management in School: Kantatararam School - งามขจรเกียรติ กชนิภา; คำสุข พานิช; บุญวิเศษ ชัยธัช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to develop an online leave management system for teachers and educational personnel at Kantatararam School to enhance the submission, tracking, and approval of leave requests in a timely and more accurate manner, while reducing reliance on paper-based documentation. The system was designed to enhance transparency and decrease errors associated with the traditional manual process. The system was developed as a web application using Visual Studio Code, with XAMPP implemented as a local server and database management environment. It supports access via computers and other devices. The system consists of three role-based access levels: (1) the user role module, which allows users to submit leave requests through online forms, track approval status, and view leave history, with automated email notifications upon approval or rejection; (2) the approver role module, which enables authorized personnel to approve or reject leave requests and receive email notifications when new requests are pending for approval; and (3) the administrator role module, which allows system administrators to add, edit, or delete user accounts and manage leave types, monitor all leave requests and approval statuses, and export summary reports in PDF and Excel formats. The findings demonstrated high efficiency and practicality for implementation within the school. It significantly improves convenience and processing, reduces procedural complexity and processing time required for leave management, enhances accuracy and transparency in data recording, and enables administrators to monitor and analyze leave statistics to support decision-making efficiently.